Effect of educational environment on the socialization of personality of a future elementary school teacher and his image (Pedagogy of Higher and Secondary Education, 2014)
Razmolodchikova I. V. Effect of educational environment on the socialization of personality of a future elementary school teacher and his image.Article considers the problem of the influence of the educational environment on socialization ofthepersonofthefutureteacher. Here is discusses processes and trends that affect on the socialization of the person teacher. Individual image is regarded as a comprehensive whole, which consists of two major components, each of them being a complex combination of various elements of knowledge and skills.
Keywords: socialization; culture; education; primary school teacher